Communicative approaches in medical discourse: based on the quarantine experience - Abduraxmanova, Madina (The Lingua Spectrum, 2025)
This article explores the distinctive features of communicative strategies and linguistic tactics manifested in medical discourse shaped under quarantine conditions. The object of analysis includes official announcements, public health advisories, warnings, and informational messages distributed by health authorities, international medical organizations, and through social media platforms during the COVID-19 pandemic. The research aims to identify pragmatic and linguistic mechanisms used to effectively convey medical information, encourage responsible behavior, and influence public awareness. Key communicative strategies are examined, including directive expressions (commands, instructions), persuasive language, cautionary statements, and diagnostic questions that engage the public in dialogue. Additionally, the study investigates the semantic, pragmatic, and etymological characteristics of medical terminology and fixed expressions widely used during the pandemic. Findings suggest that medical discourse functioned not only as a medium of information delivery but also as a powerful tool for shaping public behavior and facilitating coordinated social communication. The precision, clarity, and accessibility of language in medical messaging proved critical for achieving public health objectives. Overall, the study concludes that medical discourse in quarantine conditions evolved into a communicative platform capable of managing collective awareness, directing social conduct, and reinforcing public responsibility in the face of a global crisis. Such insights contribute to a deeper understanding of the socio-linguistic dynamics inherent in health-related communication during emergencies.